UJI KELAYAKAN “ARBARU: APLIKASI AUGMENTED REALITY BANGUN DATAR DAN BANGUN RUANG” DALAM MENINGKATKAN MINAT BELAJAR MATEMATIKA DI SEKOLAH DASAR - Clara Devi Anggraini, Cicilia; Wiradharma, Gunawan; Budiwati, Yulia; Aditya Prasetyo, Mario; Kristiana Dewi, Danar (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Students can understand the material and visualize the spatial form of mathematical objects through the use of augmented reality as an alternative learning media. The previous year the development of ARBARU was carried out: Augmented Reality Flat and Spatial Shapes applications that can be used in elementary school level math lessons. Before being used by the public, the application was tested through a questionnaire to 25 respondents from elementary school students and 15 students from the Open University PGSD Study Program. The assessment includes aspects of appropriateness of content, appropriateness of presentation, suitability of language, AR technology, usefulness, visual and audio appearance, ethnomathematics content, as well as software implementation and engineering. The empirical feasibility test is designed to evaluate the media's feasibility and ascertain the opinions of users of the mobile learning application that has been developed. The tested product is considered to meet very high standards and is suitable for use as a learning medium for space-building material, which can enhance spatial ability and comprehension of planar and space-shaped materials.